X-rays from relativistic electrons crossing a multilayer nanostructure; Nuclear Instruments and Methods in Physics Research Section B: Beam Interactions with Materials and Atoms; Vol. 227, iss 1-2 - Nasonov N. N.; Kaplin V. V. Valeriy Viktorovich; Uglov S. R. Sergey Romanovich; Zabaev V. N. Viktor Nikolaevich; Piestrup M. A.; Gary C. K. (2005, 2005)
Title screen